Unusual case of childhood tuberculosis: Clinical report and literatura review. - Martínez Córdoba, Natalia; Pilar Guerrero; Cámilo Sánchez Martín; Andrea Rangel; Marco Luciano Charry (British Journal of Healthcare and Medical Research, 2023)
Introduction: Tuberculosis of the central Nervous system occurs more frequently in children under three years of age and in immunodeficient populations, in which it is usual that it manifests as a disseminated disease, the frequency is usually higher in countries with a high prevalence of tuberculosis, and its presentation is related to a period of rapid dissemination of the germ that can occur during the first year, with the first infection. Case: 3-year-old girl with a history of latent tuberculosis who presented acute symptoms of eyelid ptosis, impossibility to adduct, and pupillary hyperactivity, with neuroimaging findings of a lesion suggestive of tuberculous granuloma, as well as bilateral mesencephalic and thalamic vascular lesions, which allowed concluding a tuberculosis involvement of the CNS. He received antituberculosis treatment with tetra conjugate, achieving clinical stability. Conclusions: The case presented describes a rare presentation of childhood tuberculosis with the finding of tuberculoma without meningitis of unusual location in the subarachnoid space and vasculitis. The diagnosis and management of this pathology, as well as a correct adherence to treatment, will have an impact on the morbidity and mortality of the patients, considering the variable clinical spectrum.